Increased Productivity and Quality Of Presto Food Production through Automatic Presto Machines - Handajani, Sri; Yunitasari, Bellina; Tjahyaningtijas, Raden Roro Hapsari Peni Agustin; Budijono, Agung Prijo; Umaroh, Susi Tri (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Presto food is one of the favorite foods of Indonesians. Some of the favorite types of presto food are grilled chicken, presto duck, fish pepes, and presto milkfish. Sidoarjo Regency is one of the regions in East Java that has an area of 15,530 hectares of ponds that produce abundant milkfish of approximately 9,866,300 tons. This is a factor in the emergence of MSMEs engaged in the culinary sector, one of which is UKM Presto Sidoarjo. Limited production equipment causes the production process to be inefficient in terms of time and fuel. Marketing that has not been widespread and product packaging that is less attractive is a factor in the product being less known to the public. The implementation method is carried out through a participatory approach, training and mentoring, as well as discussion activities between the proposing team and partners. The result of this activity is the creation of an automatic presto machine that is able to increase production capacity from 5 kg per process to 10 kg per process and the formation of partners who are independent in using the machine and increasing sales turnover through marketing on social media and product packaging that has good, creative elements, imprints on consumers and labels.